PENENTUAN KANDUNGAN ANTIOKSIDAN DALAM RIMPANG KENCUR YANG DIEKSTRAKSI DENGAN BANTUAN GELOMBANG ULTRASONIK - Refilda Suhaili (Universitas Jambi, Fakultas Sains dan Teknologi, Program Studi Kimia, 2018)
Kaempferia galanga L. rhizome is used a traditional medicine and as seasoning. Kaempferia galanga L. rhizome has many bioactivies beneficial to antioxidant. Extraction of antioxidant by maceration method takes a long time and the extraction process is not perfect so ultrasonic assisted extraction (UAE) are used to accelerate the extraction process. The propose of the research is to extract antioxidant from Kaempferia galanga L. rhizome by UAE and to determinate the antioxidant content by 1,1-diphenyl-2-picrilhydrazyl (DPPH) method. The optimum condition for extraction were 20 mL methanol as the solvent, the weight of sample 1,5 g, and extraction time 60 minutes. The total antioxidant content from Kaempferia galanga L. rhizome extraction by maceration and UAE were 0.6688 ± 0.02 and 0.8126 ± 0.02 mg/g DW. This study also validated the method of determining the total antioxidant content extracted with ultrasonic. The results of the method validation obtained linearity (r) = -0.9984, LoD value = 0.0283 mg/L, LoQ value = 0.0947 mg/L, precision (SDR = 1.97% and HORRAT = 0.96) and percent recovery 103.21%. Based on the method validation value, it can be said that the determination of the total antioxidant content in the kencur rhizome extracted with the help of UAE can be applied.